Writing skill enhancement when creating narrative texts through the use of collaborative writing and the Storybird Web 2.0 tool* - Herrera, Yeison Edgardo (Colombian Applied Linguistics Journal, 2013)
The purpose of this article is presenting how the use of Collaborative Writing (CW) through Storybird, a web 2.0 tool which promotes the creation of stories collaboratively, led two groups of learners to improve certain specific aspects of their writing skill. Both groups, the former one with fifteen students and the latter one with ten students, were about to complete a two-year general English course at Instituto de Lenguas de la Universidad Distrital (ILUD) in Bogotá, Colombia. Although their English language proficiency was expected to be at an upper-intermediate level (B2) according to the Common European Framework of Reference for languages (CEFR), their writing skill was below average. Two pedagogical interventions were performed at two diferent times, the first one from October to November 2010, and the second one from March to April 2011. Pre and posttests, focus groups, surveys and reflective journals were used and data was analyzed following coding procedures. The findings revealed that the CW supported with Storybird encouraged learners to create narrative texts and their positive attitude towards the production of stories increased. Moreover, an improvement in learners’ vocabulary and increased attempts to use complex language forms to write were noticeable.